A Meta-Analytic Review of Mental Health Interventions Targeting Youth with Internalizing Disorders in Juvenile Justice Facilities. Issue 3 (3rd July 2019) - Kumm, Skip; Maggin, Daniel; Brown, Christerralyn; Talbott, Elizabeth
ABSTRACT: There is general agreement in the research literature that youth in juvenile justice facilities are more likely to experience mental health disorders than their general population peers. The purpose of this systematic review and meta-analysis was to evaluate the methodological characteristics and effectiveness of mental health interventions delivered in juvenile justice settings on symptoms associated with internalizing disorders. The 11 studies included in the current review incorporated pretest-posttest research designs and were conducted with juveniles in secure facilities that reported outcome measures of depression, anxiety, posttraumatic stress disorder, or internalizing disorders. Meta-analytic findings indicate mixed results for interventions affecting internalizing symptoms and varying results between studies implementing an experimental design compared to those using a single group non-experimental design. Additionally, no studies examined how interventions could be incorporated into daily activities in juvenile justice facilities, such as school and classroom activities. Lastly, the limited number of studies included in the current review indicates a continued need for further experimental research on the effectiveness of mental health interventions delivered to youth in juvenile justice facilities.